Desain Gas Lift Dengan Metode Continuous Flow Untuk Mendapatkan Laju Alir Optimal Pada Sumur “F-1” Lapangan “X” - Muhammad Vijaya Waluddin; Deny Fatrianto Edyzoh Eko Widodo; Amiruddin; Andry Halim; Firdaus; Michelle Rafael Waw; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
Over time the flow rate will decrease so that the reservoir pressure will decrease, so it is necessary to optimize or increase the flow rate. To overcome the above, an artificial lift is used or what is called an “Artificial Lift”. Artificial Lift is an artificial lift method that is useful for adding pressure to the fluid so that it can flow up to the surface. At this well, the initial Artificial lift Design is being carried out using ESP (Electrical Submersible Pump) to become a Gas lift with the Continuous flow method. The purpose of this analysis is to see the potential installation of a continuous flow gas lift in the “F-1” well. The result of the IPR curve analysis from the calculation show that the “F-1” well has a maximum flow rate of 6704.7 bfpd. So that the well can still be optimized with the Gas lift design. Based on the Gas lift design, the desired flow rate is 5300 bfpd. In the F-1 well, it is known that the injection gas is 1,355,600 scf/day. As well as the location of the depth of valve 1 is at a depth of 2100 ft, valve 4 is at a depth of 2500 ft, valve 5 is at a depth of 2850 ft ( operation valve), and additional valves can be installed BE1 at 2344 ft and BE2 at 2489 ft.